ANALISIS DAN PERANCANGAN VLAN PADA DISHUBKOMINFO KABUPATEN MANGGARAI MENGGUNAKAN CISCO PACKET TRACER - Yosefina Pantu; Catur Iswahyudi; Rr Yuliana Rachmawati K (Jurnal Jarkom, 2015)
Department of Transportation, Communication and Information of Manggarai Regency, is one of the instance of Regional Government of Manggarai, NTT, which is responsible to help the Head of Region concerning transportation, communication and information affairs. The lackness of human resources which was competent in computer networking, the high cost of VSAT IP Broadband internet service and maintenance cost of network’s backbone which is wireless based, have been becoming a problem to the Department concerning their main duties. As an impact, it is necessary to the Department to change their network’s backbone to wired network based, using VLAN. VLAN can divide network into several segments with low cost implementation. The using of VLAN Trunking Protocol (VTP) will ease the network administrator in managing VLAN. The VLAN design in this study used hierarchical model. The logical layer for data distributing was divided into two layers, core/distribution and access layer. Routing between VLANs used “router-on-a-stick using trunk” model, so that the workstations which were owned by different VLAN can communicate each other by using one router only. By using simulation method for testing the design, it was discovered that all workstations between different VLAN have been successfully connected each other and all servers were well-functioned.